A vector control technology of waterjet propelled crafts using synchronous and mirror-equiangular thrust control strategy. (1st July 2020) - Jiang, Jiabing; Ding, Jiangming; Wang, Xudong
Abstract: Vector control technology with single joystick for ship maneuvering is investigated on waterjet propelled crafts for excellent maneuverability and easy manipulation. In this paper, a vector control strategy of ship motion based on synchronous thrust adjustment of two waterjets with mirror-equiangular magnitude which takes the hull cross section as the benchmark was selected firstly. Then the relationship among three manipulation parameters of joystick, six operation parameters of two sets of waterjet propulsion systems, and three motion parameters of hull was established to obtain the vector correspondence between joystick operation and hull motion. On this basis, a vector controller prototype was constructed and mounted on a ship model propelled by two sets of waterjets. The vector control functions of the lateral motion, spot turn and other complex motions such as sectorial motion were realized successfully. The technology of single joystick vector control can be applied to many operation conditions of waterjet propelled crafts, such as berthing, entering and leaving port, position operations at sea, and tactical maneuver to improve the maneuverability and safety of ships. In addition, the vector control function can also be applied to the motion control module for low-speed maneuvering condition of smart ship. Highlights: Based on the mathematical & numerical research and model test, a vector control technology for waterjet ship is proposed. The mathematical model is developed based on synchronous and mirror-equiangular thrust control strategy. The accuracy and effect of vector control are improved by combining the numerical analysis. Vector control prototype can realize vector control function in calm water and wave.